Evaluating subalpine lake delta carbon storage in the Colorado Front Range and Washington Central Cascades - Scott, Daniel, author; Wohl, Ellen, advisor; Bledsoe, Brian, committee member; Rathburn, Sara, committee member (Colorado State University. Libraries, 2015)
Mountainous regions are important contributors to the terrestrial organic carbon (OC) sink that affect global climate through the regulation of carbon-based greenhouse gases. However, mountain OC dynamics are poorly quantified. I sought to explore OC storage in subalpine lake deltas in the Washington Central Cascades and Colorado Front Range with the objectives of determining the magnitude of carbon storage and understanding the differences in storage between the two ranges. I used field, laboratory, and GIS techniques to determine the magnitude of and controls on the subaerial portion of the subalpine lake delta OC sink in 26 subalpine lake deltas, 14 in the Front Range and 12 in the Cascades. Soil moisture, texture, and delta valley confinement are significantly correlated with soil carbon on deltas. Average soil OC content on subalpine lake deltas ranges from 3 to 41%, and 140 to 1256 MgC/ha. Surprisingly, the carbon stocks of subalpine lake deltas are not significantly different between regions. I present a conceptual model that invokes basin-scale carbon dynamics to offer an explanation for how two regions with very different climate and tectonics have unexpectedly similar carbon stocks in their subalpine lake deltas. This conceptual model suggests that carbon is more likely to reach subalpine lake deltas from the upstream basin in the Colorado Front Range compared to the Washington Central Cascades. This points to a complex interaction among carbon production, transport, and stability in each region, and supports the idea that mountainous regions are complex carbon reactors.